Wormhole solutions and energy conditions in f(R; T ) gravity with exponential models - Ghulam Mustafa; M. Farasat Shamir; Anum Fazal (Kuwait Journal of Science)
In the present article, we examine the solutions of the wormhole by using inhomogeneous spacetime in modified $f(R,T)$ theory of gravity. We take two dissimilar models of $f_{1}(R)$ that are $f_{1}(R)=R-αγ(1-e^{-\frac{R}{γ}})$ known as exponential gravity model and $f_{1}(R)=R-αγ tanh(\frac{R}{γ})$ known as Tsujikawa model, where $α,~γ$ are model parameters. We explore the feasible solutions for these models. Moreover, we discuss analytically as well as graphically, different properties of these model of wormholes by giving suitable values to the model parameters. We then consider two specific shape functions i.e. $F_s(r)=r_0\frac{Log(r+1)}{Log(r_0+1)}$ and $F_s(r)=\frac{r}{e^{r-r_0}}$ and energy conditions have been explored using the above mentioned two models. Conclusively, we find that obtained wormhole solutions are physically acceptable with the considered exponential and Tsujikawa gravity models with or without the presence of exotic matter.